2018
DOI: 10.1159/000488241
|View full text |Cite
|
Sign up to set email alerts
|

What Is the Role of Barbed Suture in Laparoscopic Myomectomy? A Meta-Analysis and Pregnancy Outcome Evaluation

Abstract: Background: This work analyzes the feasibility and effectiveness of barbed suture during laparoscopic myomectomy. Methods: Eight works have been carefully examined for the meta-analysis from all papers published online until November 2017. Results: Barbed suture proved to be superior to traditional suture technique in blood loss in laparoscopic myomectomy (Standardized Mean Difference [SMD] –0.650, 95% CI –1.420 to –0.119, p = 0.098, test for heterogenity p < 0.0001, I2 = 95.54%), Hb drop (SMD –1.45… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 43 publications
1
25
0
Order By: Relevance
“…The unidirectional barbed thread, a novel absorbable thread without knots, can decrease the laparoscopic suturing difficulty and improve the suturing speed by enabling the running sutures without knots [16]. To date, the barbed suture has been used in a variety of surgical fields, including urology department [1719], gynecology department [20,21], oncology department [22], and general surgery department [2325]. The purpose of this study was to evaluate the efficacy and safety of TTD, common suture, and barbed suture after LCBDE for choledocholithiasis, and to provide more evidence for selecting the optimal duct closure method after LCBDE.…”
Section: Introductionmentioning
confidence: 99%
“…The unidirectional barbed thread, a novel absorbable thread without knots, can decrease the laparoscopic suturing difficulty and improve the suturing speed by enabling the running sutures without knots [16]. To date, the barbed suture has been used in a variety of surgical fields, including urology department [1719], gynecology department [20,21], oncology department [22], and general surgery department [2325]. The purpose of this study was to evaluate the efficacy and safety of TTD, common suture, and barbed suture after LCBDE for choledocholithiasis, and to provide more evidence for selecting the optimal duct closure method after LCBDE.…”
Section: Introductionmentioning
confidence: 99%
“…Surgery technical complexity is reduced too, as it is widely believed that laparoscopic sutures are one of the most difficult and time-consuming tasks during endoscopic surgery (29,30). Finally, perioperative complications such as nosocomial infections or organic stressed events are diminished, as well as hospital stay; shorter hospitalization positively affects patients' physical and emotional quality of life, and may reduce hospital assistance costs too (31,32). Despite all the previously mentioned benefits, barbed suturerelated complications must be carefully considered.…”
Section: Discussionmentioning
confidence: 99%
“…Barbed sutures were designed with the intent to decrease the surgical time by eliminating the need for tying surgical knots, which was successfully demonstrated in the subgroup analysis of this review. Similar results with regards to its efficacy have been demonstrated in suture‐intensive laparoscopic gynecological surgeries such as hysterectomy and myomectomy 13,14 . A meta‐analysis analyzing the effectiveness of barbed sutures in laparoscopic myomectomy showed a statistically significant decrease in suturing time (standardized mean difference [SMD] −1.97, 95% CI −1.85 to −0.55, P ≤ .001) and total operative time (SMD –0.687, 95% CI –0.804 to –0.569, P ≤ .001) 13 .…”
Section: Discussionmentioning
confidence: 99%
“…Similar results with regards to its efficacy have been demonstrated in suture‐intensive laparoscopic gynecological surgeries such as hysterectomy and myomectomy 13,14 . A meta‐analysis analyzing the effectiveness of barbed sutures in laparoscopic myomectomy showed a statistically significant decrease in suturing time (standardized mean difference [SMD] −1.97, 95% CI −1.85 to −0.55, P ≤ .001) and total operative time (SMD –0.687, 95% CI –0.804 to –0.569, P ≤ .001) 13 . Another systematic review concluded that compared with the use of conventional suture, the total operative time of laparoscopic myomectomy (SMD −0.58; 95% CI, −0.88 to −0.28) and the suturing time to close the uterine incision (SMD −1.38; 95% CI, −1.86 to −0.90) were significantly reduced with the use of barbed sutures.…”
Section: Discussionmentioning
confidence: 99%